Implementasi Pembelajaran Gradasi Warna Model Discovery Learning Untuk Mengembangkan Kreativitas Siswa Kelas 3 MI Attarbiyatul Islamiyah - Nailil Amaliyah; Naily Faridatus Soraya; Naily Najwa Kamalia; Farah Aliya Zelikha; Senly Anjely Robby; Rakanita Dyah Ayu Kinesti (FKIP Universitas Wiraraja, 2026)
This study aims to examine the implementation of color gradation learning using the Discovery Learning model to enhance creativity among third-grade students at MI Attarbiyatul Islamiyah. A qualitative descriptive approach was employed, with the population consisting of third grade students and teachers at the school, and the sample focusing on the third-grade class teacher and students. Data collection instruments included interviews, observations, and documentation, validated through method and source triangulation, with analysis involving data reduction, presentation, and conclusion drawing. Findings reveal that the six stages of Discovery Learning: stimulation, problem statement, data collection, data processing, verification, and generalization were effectively applied, resulting in improved student understanding of color gradation techniques, heightened motivation, active exploration, and significantly enhanced creativity in producing harmonious artworks. Students shifted from flat coloring to innovative color blending and expression, fostering cognitive, psychomotor, and affective development, though some required additional guidance for focus and precision.